Synthesis of β-FeSi2/Si heterojunctions for photovoltaic applications by unbalanced magnetron sputtering - Tatar, B.; Kutu, K.; Uergen, M. (ELSEVIER SCIENCE SA, 2007)
We report here the possibility of the growth of semiconducting FeSi2 layers on Si(100) substrates by depositing iron with unbalanced magnetron sputtering. The originality of the study is the achievement of heterojunction without any further treatment of the deposited films. Pure iron is deposited on Si(100) substrates with unbalanced magnetron sputtering for the production of beta-FeSi2/Si heterojunctions. Prior to coating process the substrates are cleaned with neutral molecular source. Microstructure of beta-FeSi2 films were investigated by X-Ray Diffraction analysis and Raman Spectroscopy. Dark current-voltage characteristic of the deposited coatings showed a rectifying behavior for the beta-FeSi2/Si heterojuctions. Open-circuit voltage (V-oc) and short-circuit current density (J(sc)) were measured under 100 mWcm(-2) illumination and a V-oc of 360 mV and J(sc) of 180 mu Acm(-2) were measured. The illumination of the silicon side gave higher photosensitivity than the illumination of the iron silicide side. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: iron disilicide; beta-FeSi2/Si heterojunctions; Raman Spectroscopy; photovoltaic; THIN-FILMS; DEPOSITION; STRESS; GROWTH; Materials Science; Physics